Research methods in political science : an introduction using microcase - LeRoy, Michael K. (Wadsworth Cengage Learning, 2013)
Use award-winning software to analyze and critically evaluate real data with the Eighth Edition of RESEARCH METHODS IN POLITICAL SCIENCE: AN INTRODUCTION USING MICROCASE EXPLORIT. This workbook includes a Windows version of MicroCase ExplorIt, a user-friendly program that makes it easy to manipulate and learn from actual data without getting bogged down in complicated statistical software. Over two dozen research-quality data files are included in this package, along with 13 exercise worksheets (one per chapter), that let you see the real impact of the concepts you study. You're then walked through the entire research process, giving you hands-on experience in research methods